Morphology of Local Sweet Potatos (Ipomoea batatas) Leave Waste in Disused Limestone Mining Areas were Fertilized by Goat Litter Compost - Doso Sarwanto; Sari Eko Tuswati (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2021)
The aim of this study was to determine the morphology of local sweet potato (Ipomoea batatas) leaf waste as forage in disused limestone mining areas were fertilized by goat compost litter. The method used in this research was an experimental method in the disused limestone mining area by using a factorial pattern with a completed randomized design, each treatment was repeated 3 times. Factor I was three types of local sweet potatoes, namely purple (U), white (P) and yellow (K) sweet potatoes, while the Factor II was the level of goat litter fertilization, namely k1: Level of goat litter fertilization 0.5 kg. / m2, k2: 1 kg / m2, k3: 1.5 kg / m2 and k4: 2 kg / m2. The morphology of sweet potato leaf waste was measuredby the number of leaf, the width of leaf, the length of leaf stalk and the weight of leaf . The results showed that the local type of sweet potato had significant different (P < 0.05) but the level of goat compost litter fertilization had no significant different (P > 0.05) on the morphology. Judging from the, it can be concluded that the waste of orange (O) sweet potato leaf with goat litter fertilization of at least 1 kg/m2 or 10 tons/ha has a high morphology, so that the amount of sweet potato leafwaste which was produced for the forage will be high.